Unlocking the Anti-Aging Potential of Apple (Malus domestica) Extract: In Vitro Modulation of TIMP-1, Casp-3, and GPX Gene Expression in Fibroblast Cells - Utami, Sri; Sachrowardi, Qomaryah Romadhiyani; Laksono, Sonny Pamuji; Rahmah, Nunung Ainur; Tunru, Insan Sosiawan; Mustaqimah, Dewi Nurul; Purwanto, Eko; Aryenti, Aryenti; Endrini, Susi; Syarif, Irfan; Ernawati, Kholis; Widowati, Wahyu; et al. (Trends in Sciences, 2025)
Ultraviolet (UV) exposure accelerates skin aging by inducing oxidative stress, apoptosis, and extracellular matrix degradation. Malus domestica (apple) extract (AE) is rich in antioxidants and bioactive compounds that may counteract these effects. This study evaluates the protective effects of AE on fibroblast cells exposed to UV radiation by assessing the expression of Tissue Inhibitor of Metalloproteinase 1 (TIMP-1), Caspase 3 (Casp-3), and Glutathione Peroxidase (GPX). Fibroblast cells were exposed to UV radiation and treated with different concentrations of AE (3.13, 6.25, 12.5 µg/mL). Gene expression levels of TIMP-1, Casp-3, and GPX were analyzed using qRT-PCR. AE significantly increased TIMP-1 and GPX expression while downregulating Casp-3 in a concentration-dependent manner. The highest concentration (12.5 µg/mL) demonstrated the most pronounced protective effects. These results suggest that apple extract enhances extracellular matrix stability, reduces oxidative stress, and inhibits apoptosis in UV-exposed fibroblasts. AE exhibits potent anti-aging properties by modulating key molecular pathways involved in skin damage. This study provides scientific evidence supporting its potential as an active ingredient in skincare formulations for UV protection and skin rejuvenation. HIGHLIGHTS Apple extract significantly upregulated TIMP-1 and GPX expression while downregulating Casp-3, indicating enhanced extracellular matrix stability and reduced apoptosis. The findings suggest that apple extract mitigates oxidative stress and inhibits apoptosis, which are key contributors to skin aging. A dose-dependent effect was observed, with the highest concentration (12.5 µg/mL) demonstrating the most significant anti-aging impact. GRAPHICAL ABSTRACT